Reports - Filipenko, Volodymyr; Shevchenko, Olena; Vasiuk, Volodymyr; Zinchenko, Anatoliy; Horpenyuk, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
Report of the societies and associations of orthopedic trauma of Ukraine.